Molecular epidemiology of tetM genes in Neisseria gonorrhoeae. Issue 1 (1st February 1999) - Turner, A; Gough, K R; Leeming, J P
Abstract : OBJECTIVE: To examine the epidemiology of the tetM gene in Neisseria gonorrhoeae strains with high level resistance to tetracycline (TRNG) using a polymerase chain reaction (PCR) assay. METHODS: A single tube PCR was developed which distinguishes between the American and Dutch variants of the tetM gene. Between 1988 and 1995, 518 strains of TRNG (tetracycline MIC > 8.mg/l) were referred to the Gonococcus Reference Unit by other laboratories or isolated from routine swabs taken at local clinics. The strains were analysed for plasmid content, auxotype, serovar, and the tetM gene type. Travel details of the patients were determined by a questionnaire. RESULTS: A PCR product was obtained from all TRNG examined. 387 TRNG strains produced a 778 bp PCR product (American type tetM) and 131 produced a 443 by PCR product (Dutch type tetM). Infections acquired in the United Kingdom contributed 57% of the TRNG strains included in this study; 82% of these carried the American type of tetM. The number of UK acquired TRNG received by the GRU increased each year except 1993--from four strains received in 1990 to 92 in 1995. After the United Kingdom, Caribbean and African countries contributed most strains, with 56 and 60 TRNG acquired in each area respectively. All strains originating in Africa, except one from South Africa, contained the American type tetM. Infections caught in Nigeria and Kenya contributed most strains (15 and 14 respectively). The TRNG originating from Caribbean countries comprised 36% Dutch tetM type. Infections caught in Jamaica accounted for 82% of the Caribbean strains. All 35 TRNG strains originating in the Far East contained the Dutch type tetM. 25 of the Far East strains were also penicillinase producing (PPNG). Infections originating in Indonesia accounted for 49% of the Far East strains but these belonged to 12 different auxotype/serovar combinations. A geographical variation in the type of penicillinase coding plasmids found in PPNG/TRNG was also detected. CONCLUSIONS: These data suggest that the Dutch type tetM may have originated in the Far East and the American type in the African continent. Subsequent spread has resulted in a heterogeneous distribution of TRNG types in other parts of the world. At completion of the survey the numbers of TRNG imported each year from the major overseas sources had reached a plateau while UK contracted TRNG continued to rise providing evidence for the establishment of endemic TRNG strains in the United Kingdom.